FLUIDITY SPEECH FORMATION AS A QUALITATIVE CHARACTERISTIC OF THE ORAL STATEMENT OF PRESCHOOL AGE CHILDREN WITH STUTTER - E. A. Borisova (Obrazovanie i Nauka, 2015)
The research objective is to disclose the subject matter of speech therapy work focused on fluidity speech formation of preschool age children, suffering stutter. Stutter is a difficult disorder of articulation organs suchthat the tempo-rhythmical organisation of statements is distressed that leads to defects and failures of dialogue system, negatively influences on individual development of the child; more specifically it generates the mental stratifications, specific features of emotional-volitional sphere, and causes undesirable qualities ofcharacter such as shyness, indecision, isolation, negativism. The author notes that the problem of early stutter correction among junior preschool-aged children considered as topical and immediate issue. Methods. Concerning the clinical, physiological, psychological and psychologic-pedagogical positions, the author summarizes theoretical framework; an experimentally-practical approbation of an author's method of speech fluidity and stutter abolition of preschool children is described. Stage-by-stage process of correction,spontaneous and non-convulsive speech formation: 1. restraint mode application in order to decrease incorrect verbal output; 2. training exercises to long phonatory and speech expiration; 3. development of coordination and movements rhythm helping to pronounce words and phrases; 4. formation of situational speech, at first consisted of short sentences, then passing to long ones; 5. training to coherent text statements. The research demonstrates data analyses of postexperimental diagnostic examination of stuttering preschool children, proving the efficiency of the author’s applied method. Scientific novelty. The research findings demonstrate a specific approach to correction and stutter abolition of preschool children. Proposed author’s approach consists of complementary to each other directions of speech therapy work which are combines in the following way: coherent speech formation corresponding to age norms; the assistance in development of lexical and grammatical means of language; development of communicative skills. Practical significance. The identified methodological recommendations while correction-pedagogical process can be used for formation of communicative children readiness to school training and gaining experience of positive interaction with people around them. Timely measures aimed at speech acquisition of stuttering preschool children can warn possible deviations in mental development and prevent many difficulties due to their social adaptation. It is especially underlined that the guarantee of successful speech therapy work on stutter correction should be aimed at active interaction of experts with teachers of preschool educational institutions and parents.